Frequency-Oriented Subsampling by Photonic Fourier Transform and I/Q Demodulation - Wenhui Hao; Yitang Dai; Feifei Yin; Yue Zhou; Jianqiang Li; Jian Dai; Wangzhe Li; Kun Xu (IEEE Photonics Journal)
Subsampling can directly acquire a passband within a broad radio frequency (RF) range, avoiding down-conversion and low-phase-noise tunable local oscillation. However, subsampling suffers from band folding and self-image interference. In this paper, we propose a frequency-oriented subsampling to solve those two problems. With ultrashort optical pulse and a pair of chromatic dispersions, the broadband RF signal is first short-time Fourier-transformed to a spectrum-spread pulse. Then, a time slot, corresponding to the target spectrum slice, is coherently optical-sampled by in-phase/quadrature (I/Q) demodulation. We demonstrate the novel bandpass sampling by a numerical example, which shows the desired uneven intensity response, i.e., prefiltering, to avoid the band folding. We show in theory that appropriate time-stretch capacity from dispersion can result in prefiltering bandwidth less than sampling rate. Image rejection due to I/Q sampling is also analyzed. A proof-of-concept experiment, which is based on a time-lens sampling source and chirped fiber Bragg gratings, shows the center-frequency-tunable prefiltered subsampling with bandwidth of 6 GHz around, as well as imaging rejection larger than 26 dB. Our technique may benefit future broadband RF receivers for frequency-agile Radar or channelization.